2017
DOI: 10.1016/j.hrthm.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic predictors of complete heart block and recovery of conduction after surgical repair of congenital heart disease

Abstract: BACKGROUND Complete heart block (CHB) is a major complication that occurs after congenital heart surgery. We hypothesized that genetic and clinical factors are associated with the development of postoperative CHB and recovery of atrioventricular (AV) conduction. OBJECTIVE The purpose of this study was to identify predictors of CHB and recovery after congenital heart surgery. METHODS Patients undergoing congenital heart surgery at our institution from September 2007 through June 2015 were prospectively enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Complete AV block is a hemodynamically important sequela and its incidence decreases to 1 to 5% from 25% with the development of modern surgical techniques and a better understanding of the anatomy of the conducting system. [ 22 - 24 ] In a study, Murray et al,[ 25 ] reported the incidence of complete AV block as 3.7%, Ayyildiz et al[ 26 ] reported as 6.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Complete AV block is a hemodynamically important sequela and its incidence decreases to 1 to 5% from 25% with the development of modern surgical techniques and a better understanding of the anatomy of the conducting system. [ 22 - 24 ] In a study, Murray et al,[ 25 ] reported the incidence of complete AV block as 3.7%, Ayyildiz et al[ 26 ] reported as 6.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital heart disease (CHD) is the most frequent type of congenital malformation with a relative incidence of 6/1000 live births and a small percentage of this CHD is related to chromosomal abnormality described in literature (1,2). An important cause of mortality and morbidity is represented by the malformation itself and by the complications which may occur in the long term (3,4). In the majority of these cases the etiology remains unknown, but among the known causes of congenital heart disease, approximately one third of cases is associated with genetic factors such as chromosomal anomalies identified in about 0.4 -26.8% of all CHD, copy number variants (CNVs), gene mutations (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…As reported previously, many gap junction and ion channel genes such as KCNQ1, KCNE1, KCNH2, KCNE2, KCNJ2, SCN5A, CASQ2, ANK2, GJA5 and HCN4 were known to relate with AVB. 1016 Besides, the structural protein TTN mutation (TTN p.Glu5365Asp;TTN p.Arg3067His; TTN p.Arg8985Cys) was reported previously to be detected among AVB patients. 6 TTN mutation was reported previously to be the genetic cause of cardiomyopathy, 17,18 one of the potential causes of AVB.…”
Section: Introductionmentioning
confidence: 92%